Specifically Targeting Metacaspases of Candida: A New Therapeutic Opportunity - Anne-Lise Bienvenu; Lionel Ballut; Stephane Picot (Journal of Fungi, 2024)
The World Health Organization (WHO) recently published a list of fungal priority pathogens, including Candida albicans and C. auris. The increased level of resistance of Candida is raising concern, considering the availability of only four classes of medicine. The WHO is seeking novel agent classes with different targets and mechanisms of action. Targeting Candida metacaspases to control intrinsic cell death could provide new therapeutic opportunities for invasive candidiasis. In this review, we provide the available evidence for Candida cell death, describe Candida metacaspases, and discuss the potential of Candida metacaspases to offer a new specific target. Targeting Candida cell death has good scientific rationale given that the fungicidal activity of many marketed antifungals is mediated, among others, by cell death triggering. But none of the available antifungals are specifically activating Candida metacaspases, making this target a new therapeutic opportunity for non-susceptible isolates. It is expected that antifungals based on the activation of fungi metacaspases will have a broad spectrum of action, as metacaspases have been described in many fungi, including filamentous fungi. Considering this original mechanism of action, it could be of great interest to combine these new antifungal candidates with existing antifungals. This approach would help to avoid the development of antifungal resistance, which is especially increasing in Candida.